La práctica de la prueba electrónica y su valoración por los jueces civiles en las audiencias orales - Sani Palacios, Yadira Nataly (2025)
The present research project focuses on the practice of digital evidence within Ecuadorian legislation to determine its characteristics, definitions, general principles, and valuation of electronic evidence by various justice operators within the Ecuadorian legal framework. The content addresses the evidentiary procedure where there are different phases to announce, produce, practice, and evaluate evidence through other means, by the General Organic Code of Processes, the Organic Law of Electronic Commerce, signatures and data messages, the Notarial Law, the Law of Digital and Audiovisual Transformation and the Constitution of the Republic of Ecuador. The research reveals a lack of approach to the regulations regarding the compilation of rules that adequately govern the practice of digital or electronic evidence. Regarding the methodology, a deductive, legal, analytical, and dogmatic approach is specified, which will be implemented through an interview guide as a research instrument to achieve the objectives set out in the research work. Finally, the contribution was made to facilitate the correct production and interpretation of electronic evidence regarding the evidentiary effectiveness in hearings, generating conclusions and discussions that contribute to society.